The treatment of drinking problems : a guide for the helping professions - Edwards, Griffith (Cambridge University Press, 2003)
The Treatment of Drinking Problems has become, over the past twenty years, the definitive text in its field. Internationally acclaimed and translated into six languages, it is the most authoritative source book for the treatment of alcohol problems for all professionals who encounter them.